Why has god created evil? a Muslim response - Bakour Mohamad, Bachar (International Institute for Muslim Unity (IIMU), 2017)
This article explores 'The problem of evil', or 'Theodicy' from an Islamic perspective. It aims to understand why evil exists, how God, the omniscient, the omnipotent and the perfectly good, allows the existence of evil and suffering in the world. This article, drawing heavily from major Muslim sources, attempts at clearing up the mystery of the matter by discussing various doctrines (the mercy and justice of God, the purpose of existence, this world vs. the hereafter, good vs. evil, necessary qualities of man, life is a trial, etc.). The article concludes that the main purpose of man’s creation is to undergo a life of test in a temporary world. This is on one hand. On the other hand, the present world is perceived as a very short episode in the long unfinished story of the entirety of life, an episode whose sole and exclusive hero is a free will man. Life is by nature imbued with numerous forms and ways of test and affliction. Further, evil-doers will be brought to divine justice which has committed itself to support the crushed and oppressed people, either in this life, or in the life to come.